Comparative study of dexamethasone versus dexmedetomidine as adjuvants to 0.25% bupivacaine in transversus abdominis plane block for post-operative analgesia in lower segment cesarean section - Padma Amar Vishal; Srikar Madugula; Bhavani P (Asian Journal of Medical Sciences, 2025)
Background: Effective post-operative pain management is essential for patient comfort and recovery after a lower segment cesarean section (LSCS). Aims and Objectives: This study compares dexamethasone and dexmedetomidine as adjuvants to 0.25% bupivacaine in TAP block for post-operative analgesia after LSCS. The objectives are to assess analgesia duration in both groups, compare pain intensity using Visual Analog Scale (VAS) scores at multiple intervals, evaluate rescue analgesia consumption within 48 h, and analyze patient satisfaction with analgesia. Materials and Methods: A randomized, single-blinded study included 60 parturients (American Society of Anesthesiologists) undergoing LSCS under spinal anesthesia. They were randomized into: Group DEXA: 0.25% bupivacaine (40 mL)+8 mg dexamethasone, Group DEXMED: 0.25% bupivacaine (40 mL)+1 mcg/kg dexmedetomidine. Pain was assessed using VAS at 0, 2, 4, 6, 12, 18, 24, 36, and 48 h. Total analgesia duration, rescue analgesic use, and patient satisfaction were recorded. Statistical analysis used SPSS 2021 (P<0.05 significant). Results: Analgesic duration was significantly longer in DEXMED (24.39±4.14 h) vs. DEXA (15.43±2.81 h, P=0.0001). VAS scores were significantly lower in DEXMED at 6, 12, 18, 24, and 36 h (P<0.0001). Rescue analgesia use was lower in DEXMED (P=0.0001). Patient satisfaction was slightly higher in DEXMED (P=0.337). Conclusion: Dexmedetomidine provides prolonged analgesia, lower pain scores, and reduced analgesic consumption, making it a superior adjuvant to bupivacaine in TAP block for LSCS pain management.